Potential and Actuall Significanance of Montessori Learning Environment - Beata Zuzanna Bednarczuk (Lubelski Rocznik Pedagogiczny, 2024)
Introduction: It is important that people who want to perform their duties in a global and uncertain reality are prepared for changes. Therefore, education can play a significant role in supporting the development of active, competent citizens. The superior task of the contemporary school is to provide an educational environment which would be a source of various experiences with the material, social and cultural world (Todd et al. 2019). The model solution in this regard is offered by the school environment organized according to Maria Montessori’s pedagogical principles. The guiding standard for such an environment is support of the individual’s potential. This is also the key rule on which the lifelong learning paradigm is based (Fleming, 2021).